Teaching Night And Fog: Putting A Documentary Flim in History - Reid, Donald (Teaching History: A Journal of Methods, 2008)
Night and Fog is the deportation seen and recounted by Christ.. .. Alain Resnais offers the left cheek and it is we who receive the slaps smack in the face, each shot being a well-deserved blow. -Fran9ois Truffaut1 I have shown Night and Fog (1956), Alain Resnais’s documentary film on the Nazi concentration camps, for twenty-five years in courses in modern European and modern world history. The film "presented the first graphic depiction of the working of the camps and of the techniques of mass murder used by the Nazis since the end of the first Nuremberg Trial in 1946."2 It is a work of memory and of history and of the ambiguities and conflicts that the interplay of these entails. Spurred by the Network of Remembrance (Réseau du souvenir) in France, composed of deported resister survivors and the families of those who had died in the camps, and commissioned by the French republic’s official Committee of the History of the Second World War to commemorate- to bring together in memory- the tenth anniversary of the liberation of the camps, Night and Fog takes viewers on the journey to the camps when they were in operation and, in 1955, when the film was made.3